The Role of Sustainability Reports in The Disclosure of Risk Management, Capital Adequacy, And Liquidity Risk To Company Value in Indonesian Banking Companies - Sheila Sheila; Herman Ruslim (PT. Publikasiku Academic Solution, 2023)
This study aims to examine the effect of risk management disclosure, capital adequacy, and liquidity risk on company value with sustainability report disclosure as a moderation variable. This research data is taken from the financial statements and annual reports of banking companies listed on the Indonesia Stock Exchange from 2018-2021. Sample selection using purposive sampling method with data of 164, testing this study using regression analysis panel data with random effect model. The results of this study show that risk management disclosure has no effect on company value, capital adequacy has a positive effect on company value, and liquidity risk has no effect on company value. In addition, sustainability reports are not able to strengthen the influence of independent variables on company value. This research is expected to be useful for the Financial Services Authority as evaluation material for improving banking company regulations. In addition, this research is expected to add information for investors to use financial statements and annual reports in decision making.